Catalytic photodegradation of pharmaceuticals - homogeneous and heterogeneous photocatalysis - Klementova, S; Kahoun, D; Doubkova, L; Frejlachova, K; Dusakova, M; Zlamal, M (Photochemical & photobiological sciences, 2017)
Photocatalytic degradation of pharmaceuticals (hydrocortisone, estradiol, and verapamil) and personal care product additives (parabens-methyl, ethyl, and propyl derivatives) was investigated in the homogeneous phase (with ferric ions as the catalyst) and on TiO2. Ferric ions in concentrations corresponding to concentrations in natural water bodies were shown to be a significant accelerator of the degradation in homogeneous reaction mixtures. In heterogeneous photocatalytic reactions on TiO2, lower reaction rates, but mineralisation to higher extents, were observed.
Keywords: verapamil; katalýza; ultrafialové záření; Catalysis; Spectrophotometry, Ultraviolet; Photolysis; hydrokortison; Titanium; léčivé přípravky; Hydrocortisone; Estradiol; fotolýza; parabeny; Verapamil; Parabens; Pharmaceutical Preparations; Ultraviolet Rays; spektrofotometrie ultrafialová; titan; estradiol